Armenian Advertising Market in the Field of Media Psychology - Grigoryan, Satenik (Bulletin of Yerevan University E: Philosophy, Psychology, 2023)
Nowadays, with a wide variety of choices available in the market, advertising is the best solution for promoting a product. Various psychological techniques are used to create effective advertising, such as brand recognition of the product, color tactics, frequency of circulation, selection of the target groups, use of a memorable and appropriate slogan, use of alternative methods, etc. The purpose of the work is a separate consideration of advertising from the point of view of its influence on a person and his value system. Nowadays, the media, saturated with multi-genre information, introduce ideas, and values into our subconscious, against which our consciousness is powerless. Advertisers do not give each other the right to create models, to determine the standards of life to which we willy-nilly submit. Watching the Armenian media, we notice that Western values are rooted in us, and it takes enough time to be able to break them and create new ones. Often the advertising market adheres to a certain policy without clear tactics, where competition plays the main role. In this struggle, the functional, psychological, value, ethical, and legislative aspects of advertising products are often ignored.